Pengembangan Lembar Kerja Peserta Didik Elektronik Menggunakan Nearpod dan Model Pembelajaran RADEC Pada Mata Pelajaran IPAS Di SD - Didi Syahrir; Syafri Ahmad; Yalvema Miaz; Hanif Al Kadri (Postgraduate, University of Mataram, 2023)
The fact that LKPD is still presented to students at school in the form of handouts printed by teachers is the inspiration for this research. The aim of this research is to create an E-LKPD product using the Nearpod application built on the RADEC platform. Development research using the ADDIE development model is this type of research. Research tools include questionnaires, tests, interviews, and documentation. The results of the elementary school level E-LKPD supported by the RADEC-based Nearpod application are classified as very valid. In the very practical field on the practicality questionnaire, both teacher response scores and student scores are very practical. The N-Gain score % test is applied to the efficacy category. So the resulting E-LKPD can be said to meet the criteria of being correct, useful and effective in improving student learning outcomes. The percentage test of the N-Gain score in the effective category is used to measure effectiveness. Therefore, it can be said that the E-LKPD implemented has fulfilled all valid, practical and effective criteria for improving student learning outcomes in science and science subjects using the Nearpod application based on radec as well as interest and enthusiasm for learning